Impact of Childhood Obesity and Psychological Factors on Sleep - Mazurak, Nazar; Cook, Jessica; Weiland, Alisa; Ritze, Yvonne; Urschitz, Michael; Junne, Florian; Zipfel, Stephan; Enck, Paul; Mack, Isabelle (Frontiers in Psychiatry, 2021)
The aim of the study was to analyze sleep duration and behaviors in relation to psychological parameters in children and adolescents with obesity seeking inpatient weight loss treatment in comparison to normal-weight children, and whether or not these variables would improve during the time course of treatment. Sixty children or adolescents with overweight and obesity (OBE) and 27 normal-weight (NW) peers (age: 9 - 17) were assessed for subjective sleep measures through self-reported and parent-reported questionnaires, as well as body weight, body composition, and psychological questionnaires. The OBE participants were assessed upon admission and before discharge of an inpatient multidisciplinary weight loss program. NW participants’ data was collected for cross-sectional comparison. In comparison to NW, children and adolescents with OBE had a shorter self-reported sleep duration and had poorer sleep behaviors and more sleep disordered breathing as reported by their parents. No change in sleep measures occurred during the inpatient treatment. Psychological factors including higher anxiety, depression and destructive-anger-related emotion regulation were moderate predictors for unfavorable sleep outcomes, independent of weight status. Children with obesity had less favorable sleep patterns and psychological factors influenced sleep in children, independent of weight. More research is needed on the relationship and direction of influence between sleep, psychological factors, and obesity, and whether they can be integrated in the prevention and management of childhood obesity and possibly also other pediatric diseases